Pengaruh Kurangnya Perhatian Orang Tua Terhadap Perkembangan Kognitif dan Sosial Emosional Anak Usia Dini di TK Al-Falah Desa Sibontar - Emrinawati; Misriani Hasibuan; Annisah Hasibuan; Putri Nabilah Hasibuan; Wahyu Sobiani Nasution; Siti Maryam Hasibuan (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the effect of parental inattention on the cognitive and socio-emotional development of early childhood at Al-Falah Kindergarten in Sibontar Village. The study used a descriptive qualitative approach, with a population of all children aged 4–6 years, teachers, and parents, and a purposive sample consisting of 15 children, 3 teachers, and 5 parents. Data were collected through observation, interviews, and documentation, then analyzed thematically. The results showed that parental inattention significantly impacted children's cognitive abilities and socio-emotional skills. Multiple linear regression analysis showed that the calculated t-values ​​of X1 = 3.12 and X2 = 2.87 were greater than the t-value of 2.06, while the F-test of 15.72 was greater than the F-table of 3.15, indicating a significant effect both partially and simultaneously. The R² value of 0.62 indicates that 62% of the variation in child development is explained by parental attention and stimulation at home. This study emphasizes the importance of parental involvement in supporting optimal child development.